Estimation of energy consumption due to different light bulb / Noramira Paiman - Paiman, Noramira (2013)
This study presents the distribution of illuminance, heat generated, potential energy saving and cost saving of lighting due to different types of light bulb in residential building. The selection of bulb were made based on different area of the house which require different illuminance level. From this experimental work, the bulbs were listed according to its performance in terms of illuminance and low heat radiation. The analysis shows that LED light bulb performs the best besides low energy consumption and cost of operation compared to incandescent, fluorescent, CFL and halogen light bulb.